BEARING CAPACITY OF SHALLOW FOOTING ON SOFT CLAY IMPROVED BY COMPACTED CEMENT DUST - Mosa J. Aziz Al-Mosawe; Bushra S. Albusoda; Azhar S. Yaseen (Journal of Engineering, 2009)
Low bearing capacity of weak soil under shallow footings represents one of construction problems. Kaolin with water content converges to liquid limit used to represent the weak soil under shallow footing prototype. On the other hand, cement dust, which can be defined as undesirable industrial waste material come from cement industry, was used to improve the bearing capacity of the soft soil considered in this research. The soft soil was prepared in steel box (36×36×25) cm and shallow square footing prototype (6×6) cm were used .Group of physical and chemical tests were conducted on kaolin and cement dust. The improvement were performed by making trench under the footing filled with compacted cement dust (at its optimum moisture content) at three depths (D=B, D=2B, D=3B), the trench had the same footing Dimensions, note that (B) represent the footing width. Pressure-settlement curves were used to predict the ultimate bearing capacity. The improvement ratio in bearing capacity was calculated by comparing the ultimate bearing capacity value when testing the kaolin alone with its value of kaolin improved with compacted cement dust at the same value of eccentricity. It is important to note that eccentricity values were chosen according to the rule of middle third of footing base(i.e.,e≤B/6). The improvement ratio was about (197%) in average value, that represent a good ratio of improvement.